CHOICE ARCHITECTURE AS A BASIS FOR PENSION SAVINGS DECISIONS - Dundure, Evija (University of Latvia, 2022)
The study analyses the findings of behavioural studies in enhancing the amount of private pension savings. The aim of the study is to summarize the findings of the scientific literature in a unified system, which allows to analyse the behavioural theories methods used by countries in facilitating people's decisions in funded private pension savings. The authors look at the process of pension accumulation from the perspective of their three stages of formation and identify the need for investor involvement in each of them. The developed unified system is tested by performing a comparative analysis of the 2nd and 3rd pension pillars in Latvia. It clearly shows the commonalities and differences between the two pillars, as well as the areas in which the methods of behavioural theories can be used.
The research was supported by the NATIONAL RESEARCH PROGRAMME “LATVIAN HERITAGE AND FUTURE CHALLENGES FOR THE SUSTAINABILITY OF THE STATE” project “CHALLENGES FOR THE LATVIAN STATE AND SOCIETY AND THE SOLUTIONS IN INTERNATIONAL CONTEXT" (INTERFRAME-LV, Project No.VPP-IZM-2018/1-0005).
Keywords: pension system; behavioral theory; choice architecture; Research Subject Categories::SOCIAL SCIENCES::Business and economics